Uji Kuat Tekan dan Kekerasan dengan Variasi Komposisi dan Ukuran Partikel pada Biobriket Tempurung Kelapa (Cocos Nucifera), Tongkol Jagung (Corn Cob) dan Kotoran Sapi - Kalsum, Ummi; Jumardin, Jumardin; Sahara (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to examine the mechanical characteristics of briquettes made from a mixture of coconut shells, corn cobs, and cow dung with tapioca adhesive. Briquettes were tested based on their mechanical properties for density using a vernier caliper and for compressive strength and hardness using a Universal Testing Machine (UTM). Samples were made in different mixture compositions with particle sizes of 60 mesh and 100 mesh. The results showed that variations in particle size and material composition significantly affected the quality of biobriquettes. Biobriquettes with a particle size of 100 mesh have higher density, compressive strength, and hardness than 60 mesh particles. The material composition with a ratio of 44:44:12 produced the best characteristics with a density value of 0.94 g/cm³, compressive strength of 9.32 kg/cm², and hardness of 41.10 HB. This study proved that biobriquettes meet the criteria as an environmentally friendly alternative fuel and have the potential to reduce biomass waste while providing efficient renewable energy.